Molecular mechanism of the intramembrane cleavage of the β-carboxyl terminal fragment of amyloid precursor protein by γ-secretase - Morishima-Kawashima, Maho (Frontiers in Physiology, 2014)
Amyloid β-protein (Aβ) plays a central role in the pathogenesis of Alzheimer’s disease, the most common age-associated neurodegenerative disorder. Aβ is generated through intramembrane proteolysis of the β-carboxyl terminal fragment (βCTF) of β-amyloid precursor protein (APP) by γ-secretase. The initial cleavage by γ-secretase occurs in the membrane/cytoplasm boundary of the βCTF, liberating the APP intracellular domain (AICD). The remaining βCTFs, which are truncated at the C-terminus (longer Aβs), are then cropped sequentially in a stepwise manner, predominantly at three residue intervals, to generate Aβ. There are two major Aβ product lines which generate Aβ40 and Aβ42 with concomitant release of three and two tripeptides, respectively. Additionally, many alternative cleavages occur, releasing peptides with three to six residues. These modulate the Aβ product lines and define the species and quantity of Aβ generated. Here, we review our current understanding of the intramembrane cleavage of the βCTF by γ-secretase, which may contribute to the future goal of developing an efficient therapeutic strategy for Alzheimer’s disease.